2015
DOI: 10.1007/s10265-015-0742-7
|View full text |Cite
|
Sign up to set email alerts
|

Clonality as a driver of spatial genetic structure in populations of clonal tree species

Abstract: Random genetic drift, natural selection and restricted gene dispersal are basic factors of the spatial genetic structure (SGS) in plant populations. Clonal reproduction has a profound effect on population dynamics and genetic structure and thus emerges as a potential factor in contributing to and modelling SGS. In order to assess the impact of clonality on SGS we studied clonal structure and SGS in the population of Populus alba. Six hundred and seventy-two individuals were mapped and genotyped with 16 nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 103 publications
3
16
0
Order By: Relevance
“…Some empirical studies suggest that clonality may indeed strengthen SGS (Reusch et al 1999;Setsuko et al 2004;Chenault et al 2011;Peng et al 2015). Recent meta-analysis on SGS pattern in clonal and non-clonal tree species suggested also that clonal species may display significantly higher SGS in their populations (Dering et al 2015).…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
See 2 more Smart Citations
“…Some empirical studies suggest that clonality may indeed strengthen SGS (Reusch et al 1999;Setsuko et al 2004;Chenault et al 2011;Peng et al 2015). Recent meta-analysis on SGS pattern in clonal and non-clonal tree species suggested also that clonal species may display significantly higher SGS in their populations (Dering et al 2015).…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…A set of 16 nuclear microsatellite markers (nSSRs) developed by van der Schoot et al (2000) and Tuskan et al (2004) and available at http://web.ornl.gov/sci/ipgc/ssr_resource.htm was used in the genotyping procedure as described in Dering et al (2015) ( Table 2). INEst 1.0 (Chybicki and Burczyk 2009) was used to estimate genetic diversity parameters at the genet level in both sexes: expected (H e ) and observed heterozygosity (H o ), number of alleles per locus (A), inbreeding coefficient of Weir and Cockerham (1984) (F IS ), and frequency of null alleles.…”
Section: Dna Extraction Genotyping and Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, intrinsic biological traits (e.g., clonality, breeding systems, life form, and regeneration strategy) as well as extrinsic biological traits (e.g., disturbance and behavior of seed dispersers) are important factors that affect SGS (Chung et al, 2004;Vekemans and Hardy, 2004;Dering et al, 2015). These processes determine in combination, interactively, or solely the intensity and dynamics of SGS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that clonality affects the SGS of tree species (Suvanto and Latva-Karjanmaa, 2005;Dering et al, 2015). Rhododendron species are reported to commonly exhibit clonal structure through layering (Escaravage et al, 1998;Naito et al, 1999;Mejías et al, 2002;Elliott and Vose, 2012).…”
Section: Introductionmentioning
confidence: 99%